2023
DOI: 10.2147/bctt.s395944
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Metaplastic Breast Cancer with Subtype Converted from Triple-Negative to HER2-Positive: A Case Report and Literature Review

Abstract: Background Metaplastic breast cancer (MBC) is an extremely rare malignant breast disease that has rarely been reported. The molecular subtype of MBC is mostly triple-negative, with a high recurrence rate and a worse prognosis. Due to its low HR- and HER2-positive rate, reports on endocrine and targeted therapy are very limited. Case report We report a case of infrequent triple-negative MBC, which, although at an early stage, quickly developed multiple recurrent lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In some studies, patients with HER2-positive MBC received HER2-targeted NAC, which led to pathological complete response [5, 12]. Wu et al [13] reported MBC with subtype converted from triple-negative to HER2-positive and the patient achieved a long progression-free survival time through chemotherapy and trastuzumab-targeted therapy after the subtype change. On the other hand, our patient had resistance to NAC with HER2-targeted drugs and anthracycline antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, patients with HER2-positive MBC received HER2-targeted NAC, which led to pathological complete response [5, 12]. Wu et al [13] reported MBC with subtype converted from triple-negative to HER2-positive and the patient achieved a long progression-free survival time through chemotherapy and trastuzumab-targeted therapy after the subtype change. On the other hand, our patient had resistance to NAC with HER2-targeted drugs and anthracycline antibiotics.…”
Section: Discussionmentioning
confidence: 99%